Evaluation Of Right Ventricular Dysfunction By Tapse In Patients Of Chronic Valvular Heart Disease - Chaturvedi, Mridul; Kumar Gupta, Basant; Rana, Mamta; Mittal, Dhruv; verma, Naveen (Journal of Neonatal Surgery, 2025)
Background: The way the right ventricle (RV) functions is key to the outcome of patients with chronic valvular heart disease (VHD). Although obtaining TAPSE by echocardiography is simple, current research linking TAPSE to clinical results in mixed VHD patients is scant, especially in low- and middle-income regions. Methods: We did a study in a hospital on 50 patients over 1 year with well-established chronic valvular heart disease seen at S. N. Medical College, Agra (April 2023 – March 2025). The patient was examined, given an NYHA grade and had echocardiography performed. According to the American Society of Echocardiography guidelines, I measured TAPSE, PASP, LA diameter and LVEF. The assessment of RV dysfunction was separated from how well global 2-D/colour and Doppler criteria were met. Results: Mean age of the participants was 50.8 years, with 58% identifying as male. Among all cases, MS and mixed MS+MR together made up the highest numbers (34 % MS and 38 % mixed MS+MR). The overall result was that 56 % of patients saw a decline in their TAPSE (below 17 mm). The Mean TAPSE decreased with each increase in NYHA class (II 17.2 ± 3.0 mm; III 15.7 ± 3.5 mm; IV 15.0 ± 1.7 mm; p < 0.01). There was a positive link between TAPSE and LVEF (r = 0.50, p < 0.01) and an inverse link between TAPSE and both LA diameter (r = –0.39, p = 0.017) and PASP (r = –0.45, p = 0.010). With an area under the curve of 0.871, using a cut-off of less than 15 mm allowed accurate prediction of severe RV dysfunction in 90.9 % of cases and correctly identified those without it in 74.4 % of cases. Conclusion: In chronic VHD, TAPSE falls in parallel with clinical heart-failure severity and correlates with key haemodynamic surrogates. A threshold of < 15 mm robustly identifies severe RV dysfunction, underscoring TAPSE’s utility as a rapid, non-invasive screening tool in resource-constrained environments.